2017
DOI: 10.1186/s41240-017-0065-9
|View full text |Cite
|
Sign up to set email alerts
|

Taurine supplementation in diet for olive flounder at low water temperature

Abstract: The objective of this study was to examine the effect of dietary supplementation of taurine for juvenile olive flounder (Paralichthys olivaceus) at low water temperature (16.4 ± 0.36°C). Fish meal (FM)-based diet was used as the control diet. Four other experimental diets were prepared by adding taurine to FM-based diet at 0.25, 0.50, 1.00, and 1. 50% (T1, T2, T3, and T4, respectively). Each experimental diet was fed to triplicate groups of fish (initial mean body weight, 19.5 g) for 10 weeks. At the end of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 56 publications
1
13
0
Order By: Relevance
“…Moreover, previous studies showed that plant protein sources' dietary high levels decreased more antioxidant enzyme activities in white shrimp (Wan et al, 2018;Xie et al, 2016). In the previous reports, the higher immune response in terms of SOD, GPx and RB activities was recorded in yellow catfish (Li et al, 2016) and olive flounder (Kim et al, 2017) diets supplemented with taurine.…”
Section: Discussionsmentioning
confidence: 87%
“…Moreover, previous studies showed that plant protein sources' dietary high levels decreased more antioxidant enzyme activities in white shrimp (Wan et al, 2018;Xie et al, 2016). In the previous reports, the higher immune response in terms of SOD, GPx and RB activities was recorded in yellow catfish (Li et al, 2016) and olive flounder (Kim et al, 2017) diets supplemented with taurine.…”
Section: Discussionsmentioning
confidence: 87%
“…In the previous studies, plasma total protein, total cholesterol, triglyceride levels, and HSI of red seabream were significantly reduced when fish were fed taurine-incorporated LFM diet in which 70% of FM was replaced with SM (Goto et al 2001). Kim et al (2017) observed that hematocrit and hemoglobin level of olive flounder were significantly enhanced by taurine supplementation to their diets. It seems that there is a discrepancy among biochemical and biometric results obtained from different studies on dietary taurine supplementations.…”
Section: Discussionmentioning
confidence: 89%
“…Taurine exerts ability to enhance immunity of fish and shellfish. For instance, innate immune responses of olive flounder were enhanced in fish by 0.25-1.0% taurine supplementation in a FM diet (Kim et al 2017). Dong et al (2018) found that dietary supplementation of taurine is important to improve the innate immunity of Chinese mitten crab (Eriocheir sinensis).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations